ACVR mutation [NM_001105.4:c.774G>T (p.Arg258Ser)] in pediatric fibrodysplasia ossificans progressiva complicated by scoliosis: a case report - Yang, Fangjun; Liu, Miaomiao; Pei, Shengtai; Huang, Jin; Wang, Huaming (Frontiers in Pediatrics, 2025)
This case report describes a 5-year-old female with fibrodysplasia ossificans progressiva (FOP), a rare and debilitating genetic disorder characterized by progressive heterotopic ossification. Initially misdiagnosed as an “aggressive chondroma” after two surgical resections, the patient developed recurrent paravertebral and iliopsoas ossification, culminating in severe functional impairment. Genetic testing confirmed a de novo pathogenic variant in the ACVR1 gene (NM_001105.4:c.774G>T; p.Arg258Ser). Management with NSAIDs and glucocorticoids yielded significant symptomatic improvement. This case underscores the critical importance of early genetic diagnosis to avert iatrogenic harm and guide appropriate conservative management.